Effect of proton radiation therapy on cardiovascular implantable electronic devices [CIED]. (3rd October 2022) - Gumuser, E; Sharif, Z; Ho, R; Allison, J; Aitelli, A; Bussiere, M; Shih, H; Mela, T
Abstract: Background: The number of cancer patients with CIED receiving radiotherapy has increased dramatically with improving life expectancy in both patients with cardiovascular disease and cancer. The advent of proton therapy adds new concern for potential malfunction in CIED devices, both due to significant neutron scatter and its use of strong magnets to focus radiation beams. Therefore, we aimed to assess the incidence of CIED malfunction secondary to proton therapy in this patient cohort. Methods: We retrospectively analyzed patients with CIED undergoing proton therapy at our institute between 2011–2021. Each device was programmed pre-treatment and monitored post-treatment according to a special protocol developed in our centre. Treatments were prescribed to doses up to 70 Gy (RBE) and delivered using either passive-scattering or pencil beam techniques. Distances between the CIED and treated volumes ranged from 10–50 cm. We analyzed baseline patient demographics, CIED demographics, CIED outcomes pre-proton therapy as well as post-proton therapy including device reset and requirement for replacement, analyzing up to most recent check. Results: Fifty-one patients with CIED underwent proton therapy during the study period. Estimated neutron dose ranged from 0.05–2.0 mSv/GyRBE for this patient cohort. Baseline demographics outlines in table 1. Of note 26/51 patients underwent proton therapy for ophthalmic malignancies, 6/51 for brain/skull malignancies. CIED comprised of 39 pacemakers and 12 implantable cardioverter defibrillators. Fourteen patients were pacemaker-dependent. Using 95% Confidence Interval, ventricular threshold, impedance, and amplitude, as well as atrial threshold and amplitude were unchanged, whereas atrial impedance measurements had a change pre- and post-proton therapy (Table 2). No patients had a device reset. One patient had a premature battery depletion three months post-radiotherapy for pancreatic cancer. Conclusions: Our findings suggest that proton therapy does not significantly impact CIED function. Whilst caution remains as further data is accrued, close monitoring, particularly with the advent of remote monitoring, of these patients should be recommended. Funding Acknowledgement: Type of funding sources: None.